The cultural iceberg - Coscia, Marina; Arriaga, Constanza Guillermina (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Many university students consider the possibility of participating in an international mobility program or working in a multicultural context, where English is used as the lingua franca. The goal of this project is to raise their awareness of cultural difference and help them understand and respect other cultures by developing their intercultural communicative competence. Students learn basic concepts related to the study of cultures, read and watch material especially selected for that purpose and discuss it in class. In small groups, they research and explore different aspects of a culture they would like to know more about and find a cultural informant. They interview this informant and finally, they share their work through a presentation and a blog which include the interview on video. They also reflect on the abilities acquired inside and outside the classroom.